Independent Curriculum Management at Public Elementary School 32 Banyuasin III, Banyuasin Regency - Devitamala Devitamala; Nur Ahyani; Mahasir Mahasir (Badan Penerbit STIEPARI Press, 2025)
This study explores the implementation of curriculum management under the Kurikulum Merdeka at SD Negeri 32 Banyuasin III, Banyuasin Regency. The purpose of this research is to examine how school leaders, teachers, and staff plan, organize, implement, and evaluate the Kurikulum Merdeka in order to improve the quality of education. A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation. The findings reveal that curriculum management at SD Negeri 32 has been conducted systematically, with active involvement of teachers and alignment with student needs and school context. However, challenges such as limited resources and varying teacher competencies still hinder optimal implementation. This research highlights the importance of continuous training, strong leadership, and collaborative efforts in successfully managing the Kurikulum Merdeka in elementary schools.